Efficacy of feed grade antibiotics in finishing diets containing distiller’ grains with solubles (DGS) - Loe, E.R.; Quinn, M.J.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rumensin and Tylan, both marketed by Elanco Products Company, have proved to be valuable feed additives when fed to finishing feedlot cattle. Rumensin was approved in the mid-1970s to improve feed efficiency and average daily gain. Rumensin frequently is used to manage digestive disturbances associated with otherwise erratic intakes of high grain diets. Tylan is fed as a preventative for liver abscesses. Rumen disorders such as acidosis and rumenitis are predisposing factors for liver abscesses. Erratic intakes of high grain diets along with poor bunk management are important factors that predispose cattle to ruminal disorders. Abscessed livers can have deleterious affects on animal performance, and in extreme situations lead to excess carcass trim and reduced carcass yields. Distiller’s grains with solubles (DGS) typically contain the protein, bran, and germ portions of the grain used in the fermentation process. In studies previously conducted at Kansas State University, corn germ fed at levels as low as 5% (dry basis) significantly reduced the incidence of liver abscesses. Since DGS also contain the corn germ, we hypothesized that a similar effect could be achieved by substituting DGS for corn. The objective of this study was to evaluate the efficacy of Rumensin and Tylan on growth performance, carcass characteristics, and carcass quality of yearling heifers fed diets based on steamflaked corn with and without 25% corn wet DGS.
Keywords: Beef; Cattle; Distiller’s grains with solubles (DGS); Rumensin; Tylan